Letter to Jane Tolmach; from Louis A. Baptista - Louis A. Baptista:::::: (1967)
The letter is an invitation to a lunch hosted by Louis A. Baptista in which various important figures would be present such as Dr. Nash; Dr.Sheel; Jack Thompson; and Ken Miller. The lunch occured in January 15, 1968 at 12:15pm in the dining room of the Bank of California.